Newborn Screening: Current Status in Alberta, Canada - Andy De Souza; Vanessa Wolan; Angie Battochio; Susan Christian; Stacey Hume; Grace Johner; Margaret Lilley; Ross Ridsdale; Kareena Schnabl; Chi Tran; Jolene Yuen-Jung; Iveta Sosova (MDPI AG, 2019)
Newborn screening (NBS) in Alberta is delivered by a number of government and health service entities who work together to provide newborn screening to infants born in Alberta, the Northwest Territories, and the Kitikmeot region of the Nunavut territory. The Alberta panel screens for 21 disorders (16 metabolic, two endocrine, cystic fibrosis, severe combined immunodeficiency, and sickle cell disease). NBS is a standard of care, but is not mandatory. NBS performance is monitored by the Alberta Newborn Metabolic Screening (NMS) Program and NMS Laboratory, who strive for continuous quality improvement. Performance analysis found that over 99% of registered infants in Alberta received a newborn screen and over 98% of these infants received a screen result within 10 days of age.